CLUSTERING FILE TERDISTRIBUSI - Yenni Astuti; Muhammad Harikem Ali Akbar (Institut Teknologi Dirgantara Adisutjipto, 2015)
The development of information technology is increasing at this time, certainly makes it easy for users of the technology itself. One of them in transferring files in a distributed manner, there are many types of files that make it difficult admin in selecting and classifying the file and then will be distributed to each - its own servers. By creating a new system that will facilitate Clustering distributed file an admin in file transfer without having to select the files to be distributed, because the system will automatically read from the file types that will be distributed on its own servers - each.